Climate change in the recent geological past and the near future. Predicting its impacts: a Review - Perisoratis, Constantinos (Bulletin of the Geological Society of Greece, 2019)
The climate changes are necessarily related to the increase of the Earth’s temperature, resulting in a sea level rise. Such continuous events, were taking place with minor and greater intensity, during the alternation of warm and cool periods in the Earth during the Late Quaternary and the Holocene periods. However, a particularly significant awareness has taken place in the scientific community, and consequently in the greater public, in the last decades: that a climatic change will take place soon, or it is on-going, and that therefore it is important to undertake drastic actions. However, such a climatic change has not been recorded yet, and hence the necessary actions are not required, for the time being.